Forecasting of Daily Outpatient Visits Based on Genetic Programming - Xiaobing Liu; Fulai Gu; Zhaoyang Bai; Qiyang Huang; Ge Ma (Iranian Journal of Public Health, 2022)
Background: The forecasting of daily outpatient visits has significant practical implications in outpatient clinic operation management, not only contributing to guiding long-term resource planning and scheduling but also making tactical resolutions for short-term adjustments on special days such as holidays. We here in propose an effective genetic programming (GP)-based forecasting model to predict daily outpatient visits (OV) in a primary hospital.